Effects of dietary soybean lecithin oil on the immunoglobulin level and fat globule size of milk in lactating sows - Baoming Shi; Chuanqi Wang; Teng Teng; Tao Liu; Xiwen Zhang; Anshan Shan (Food and Agricultural Immunology, 2019)
This study was conducted to investigate the effects of dietary soybean lecithin (SL) on immune function and milk quality in lactating sows. The dietary treatments included a control group and three groups that replace soybean oil with 1%, 2% and 3% SL respectively in the diets. The weight of piglets at weaning and the average daily gain (ADG) were increased by supplementation of 3% SL (P < 0.05). The content of phisphatidylcholine in milk was increased by supplementation of 2% and 3% SL (P < 0.05), and the average diameter of milk fat globule was decreased by supplementation of 1%, 2% and 3% SL (P < 0.05). The immunoglobulin levels of milk and plasma were enhanced when 2% or 3% SL was added (P < 0.05). Collectively, dietary SL decreased the milk fat globule size and improved the content of phospholipid in milk, as well as enhanced the immunoglobulin levels in milk and plasma of sows and piglets.